2002
DOI: 10.1063/1.1503774
|View full text |Cite
|
Sign up to set email alerts
|

Isotope effects in linear dihydrogen bonded complexes containing LiH

Abstract: An ab initio study of linear dihydrogen-bonded complexes containing LiH (acting as a proton acceptor) was undertaken. The complexes studied were LiH⋯HF, LiH⋯HCN, and LiH⋯HCCH. Equilibrium geometries and harmonic vibrational frequencies were computed at various levels of theory using a 6-31++G(d,p) basis set. It was found that the LiH⋯HF complex was not stable at all levels of theory. The relative stabilities of H-bonded and D-bonded isotopomers of LiH⋯HCN and LiH⋯HCCH were determined by differences in zero-poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
3
10
0
Order By: Relevance
“…[33] This result supports the conclusion that the strength of dihydrogen bond has a positive relation to the acidity of hydrogen proton in the proton donor. [31] The DE corr of the dihydrogen bond of trimer I increases by about 26 % relative to that of dimer I.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…[33] This result supports the conclusion that the strength of dihydrogen bond has a positive relation to the acidity of hydrogen proton in the proton donor. [31] The DE corr of the dihydrogen bond of trimer I increases by about 26 % relative to that of dimer I.…”
supporting
confidence: 85%
“…The initial structures of the LiH-HCN-HCN and LiH-HCN-HCN-HCN complexes ( Figure 1) were based those obtain in previous studies of LiH-HCN [29,33] and HCN-HCN. [15,16] The geometries of the complexes and their monomers were initially optimized at the MP2/6-311 + + GA C H T U N G T R E N N U N G (2d,2p) level.…”
Section: Computational Detailsmentioning
confidence: 99%
“…It is found that there is no fundamental difference between the properties and nature of dihydrogen bonds and those of conventional hydrogen bonds. For example, the strength of dihydrogen bond has a positive relation with the proton acidity of the proton donors as does conventional hydrogen bond [9,28]. However, no study on the effect of methyl group on the properties of dihydrogen bonds has been reported.…”
Section: Introductionmentioning
confidence: 97%
“…The dihydrogen bond is enhanced when the reactivity of metal hydrides is increased [3,4]. The usual proton donors in dihydrogen bonds are FH, OH, and NH groups [5][6][7], like those in conventional hydrogen bonds, although the dihydrogen bonds with CH and SH groups acting as a proton donor have also been reported [8][9][10][11][12]. The binding distances between the two interacting hydrogen atoms are typically 1.7-2.2 Å [13], significantly less than the sum of the van der Waals radii for the two hydrogen atoms (2.4 Å).…”
Section: Introductionmentioning
confidence: 99%
“…Series of gas phase studies of dihydrogen-bonded systems can be found in literature (see for example [6][7][8][9][10][11][12][13][14][15][16][17] as the most recent studies). One of the MH molecules mostly used is LiH, where the hydrogen atom has clear hydride behaviour, holding a charge about −0.8 au.…”
Section: Introductionmentioning
confidence: 99%